04 - ENERGY PROFILE OF CYSTIC FIBROSIS OF PANCREAS – MUCOVISCIDOSIS, WITH RYODORAKU ELETRODIAGNOSTIC IN ACUPUNCTURE (Fiep Bulletin - online, 2011)
This study aimed to determine the energy profile of patients with Cystic Fibrosis (CF), using the technique of Ryodoraku electrodiagnostic in Acupuncture. This assessment is a method of reading bioelectrical (impedance) on specific points of the body, the results of evaluating the Acupuncture meridians and translate the so-called energy imbalance. Fifteen volunteers were evaluated between 4 and 47 years, CF (mucoviscidosis or). In 100% of the sample was obtained by energy imbalance technique Ryodoraku electrodiagnostic, and the meridian of the Spleen (SP) showed imbalance in 67% of the volunteers followed by the Kidney meridian (KI) and Heart (H) with 40% ; Sanjiao (SJ) and Bladder (B) with 33%; Gallbladder (GB) and Stomach (ST) with 23% Small Intestine (SI), Large Intestine (LI), Pericardium (PC) and Liver (LR) with 20% and Lung (L) with 7%. It follows that the more often unbalanced meridian was the Spleen (BP), which leads us to believe that the energy source is located there, although the main symptoms of shock and organ is the lung.
Keywords: Cystic Fibrosis; Ryodoraku Electrodiagnosis; Acupuncture